Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Mukayat Mukayat; Mahfud Junaedi (Journal on Education, 2025)
This study aims to determine the effect of the implementation of the Problem Based Learning (PBL) learning model on the learning outcomes of Islamic Religious Education. Before the implementation of the PBL model, the average student score was 55, with 16.6% of students achieving scores above the KKM (70). In cycle I, the average score increased to 60, with 33% of students achieving scores above the KKM. The results of observations of student and teacher activities showed sufficient scores, namely 70 and 66, respectively. In cycle II, the average score reached 65, with 50% of students getting scores above 70. Observations of student and teacher activities showed an increase to 76 and 80, respectively. In cycle III, the average student score increased significantly to 84, with 83% of students achieving scores above the KKM. The results of this study indicate that the implementation of the Problem Based Learning learning model can significantly improve the learning outcomes of Islamic Religious Education